USM PHD STUDENT WON BEST ORAL POSTER PRESENTATION AWARD AT GENEVA HEALTH FORUM 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
GENEVA, May 2016 Lyna Irawati, a PhD student from the School of Pharmaceutical Sciences, Universiti Sains Malaysia (USM), was the only Malaysian delegate selected from young researchers around the world to present her research at the Geneva Health Forum held from 1921 April 2016 at the International Conference Centre of Geneva, Switzerland.